Radiotherapy Risk Estimation Based on Expert Group Survey - Koo, Jihye; Shin, Dong Oh; Lim, Young Kyung; Park, Soah; Rah, Jeong Eun; Hwang, Ui Jung; Kim, Dong Wook (Frontiers in Physics, 2019)
Although current quality assurance systems such as Task Group 142 of the American Association of Physicists in Medicine and other methods used for radiotherapy have greatly contributed to decreasing radiotherapy incidents, there is still scope for improvement. In this study, we attempted to evaluate the reliability of the risk priority number, which was suggested by the AAPM Task Group 100, when it was calculated by an expert group in Korea. By doing this, we aimed at providing preliminary data for applying Failure Modes and Effect Analysis (FMEA), a systematic approach to identify potential failures in Korea. For this purpose, 1163 incidents data in the Radiation Oncology Safety Information System (ROSIS) database were used. The incident data were categorized into 144 items to create a questionnaire. The expert group consisted of 19 physicists who evaluated the occurrence (O), severity (S), and detectability (D) of each item on a scale from 1 to 10 according to the AAPM Task Group 100. Among these three factors, the values of ‘O × D’ were compared with ROSIS data. When comparing the O × D value between the items ranked in the top 10 of the survey and ROSIS data, no items were duplicated, and ‘simulation’ and ‘treatment’ were most frequent among, in total, eight processes. The average difference of O × D between the survey and ROSIS data was 0.8 ± 1.5, and this difference barely followed a Gaussian distribution. The results of this work indicates that FMEA is a good predictor, but that there were still deviations between actual risk and expectations in some cases, because actual incidents are multifactorial rather than simply proportional to D and O. Further research on radiotherapy risk estimation is needed.